2013
DOI: 10.1111/trf.12272
|View full text |Cite
|
Sign up to set email alerts
|

Molecular HPA genotyping by microarray in Brazilian blood donors

Abstract: Allele frequencies were comparable to those described in other Brazilian studies. Rare HPA-9 alleles were described in Brazilians for the first time. A mutation near the HPA-2 polymorphism suggests that complementary methods might be necessary in specific cases. PLT genotyping by microarray proved to be fast, accurate, and reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
2
14
2
Order By: Relevance
“…(; HPA‐1 to 5), a group of platelet donors studied by Conti et al . (; HPA‐1 to 5 and 15), and the sample blood donors analysed by Chiba et al . (; HPA‐1 to 4).…”
Section: Resultsmentioning
confidence: 99%
“…(; HPA‐1 to 5), a group of platelet donors studied by Conti et al . (; HPA‐1 to 5 and 15), and the sample blood donors analysed by Chiba et al . (; HPA‐1 to 4).…”
Section: Resultsmentioning
confidence: 99%
“…HPA‐3 frequencies described previously for São Paulo blood donors (Conti et al , ), Brazilian African descendants (Castro et al , ) and Slovenian and Swiss descendents (Boehlen et al , ) did not differ from results found in the Amazonas blood donors. This system was one of the most polymorphic systems found in this population, after HPA‐15, with 24·99% of mismatch probability.…”
Section: Discussionmentioning
confidence: 41%
“…It is related to the degree of variability in HPAs between donors and recipients, whose frequencies vary among different populations worldwide. Among the Brazilian population, considerable data on HPA prevalence is available for Caucasians, those of African descent and Amazonian Indians (Castro et al , ), as well as blood donors (Conti et al , ; Mangerona et al , ). However, the allele frequency data among Amazonian blood donors is still lacking.…”
mentioning
confidence: 99%
“…Platelet genotyping was performed using a BeadChip assay 17, 18. The BeadChip microarray method is capable of determining 22 allelic variants of 11 HPA systems (HPA-1 to HPA-9, HPA-11 and HPA-15).…”
Section: Methodsmentioning
confidence: 99%